Video Assisted Thoracoscopic Treatment of Pleuropericardial Cysts. Issue 2 (2001) - Hermens, F. H. W.; Visser, F. J.; Termeer, A.; Barendregt, W. B.; Janssen, J. P.
Abstract : Question of the Study In this study, safety and feasibility of thoracoscopic fenestration of pleuropericardial cysts under local and general anaesthesia is evaluated. Besides, a rare case of a pleural cyst, causing a superior vena cava syndrome, is described. Materials, Patients and Methods In a retrospective study, the results of thoracoscopic treatment of pleuropericardial cysts in three patients are presented. We performed videothoracoscopic fenestration of pleuropericardial cysts. One of these was performed under local anaesthesia. The two other cases were performed under general anaesthesia. After fenestration, talc poudrage of the inner lining of the cysts was performed in one case. Results Thoracoscopic fenestration appeared to be safe and effective. No recurrence was observed. One patient was lost to follow-up. Answer to the Question Thoracoscopic fenestration of pleuropericardial cysts is safe and effective. This procedure can be performed under local anaesthesia in selected cases. The role of talc poudrage of the cysts is unclear and needs further investigation.